ASSESSMENT OF AWARENESS OF DIABETIC RETINOPATHY AMONG PATIENTS WITH DIABETES MELLITUS ATTENDING THE CARE DIABETES CENTER - Thunla, Prathyusha; Vidyasagar, Sharon; N, Kavya; Seema, Shaik (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of the study is to assess the level of diabetes mellitus patients’ awareness about diabetic retinopathy and their action toward getting screening tests and follow-up visits. Methods: Diabetes mellitus patients who attended the care diabetes center were administered a questionnaire to assess their awareness of diabetic retinopathy and the need to have a routine screening and follow-up care for disease. Results: A total of 300 diabetes patients were included in the study. Of the enrolled patients; 143 (48%) were males and 157 (52%) were females. Patients who believed that diabetes could affect their eyes are of 78%, controlling the blood sugar levels can help preserve vision 53%, and diabetes can lead to blindness 24%. Only 8% people claimed to be familiar with diabetic retinopathy. When asked whether it was important for diabetes patients to have their eye check-up, annually 62% of patients answered yes. However, only 33% of patients get their eyes checked annually. When asked about barriers preventing patients from getting eye screening, lack of knowledge about diabetic retinopathy scored more 44%. Conclusion: Although most of the subjects of this study knew that diabetes mellitus can affect the eye and that better control of diabetes mellitus can preserve their vision, only a few people are aware that diabetes can lead to blindness and what diabetic retinopathy is. Moreover, most of the patients reported that the barrier preventing them from getting eye screening is a lack of knowledge about diabetic retinopathy. Due to the lack of knowledge, patients are not having appropriate screening and management of diabetic retinopathy. These findings show the need for increasing the awareness of diabetic retinopathy among diabetic patients and the importance of annual ophthalmic eye screening.